Job pressures affecting the quality of teachers’ performance at the College of Physical Education and Sports Sciences/University of Baghdad - Salah Wahhab Shakir,; Magda Abdel-Ilah Abdel-Sattar,; Thaker Mahfoodh Hamed al- Dulaimi, (Eximia, 2024)
The research aimed to prepare a measure of job stressors affecting the quality of teaching performance in the College of Physical Education and Sports Sciences at the University of Baghdad, to identify their levels, if any, and the most influential dimensions on the quality of teaching performance within the college’s work environment, as well as the deanship’s ability to help prevent and Alleviating its severity through logical administrative methods, on a scale that includes four dimensions that include (the administrative and financial environment, the organizational environment, the social and humanitarian environment, and the scientific and research environment). The descriptive approach was adopted using the case study method for a sample of (166) teachers from the original community of (182) teachers, with a percentage of (91.209%). The research results were processed using the statistical package system (SPSS), version (V28), (statistical package for social sciences). The results showed that teachers were exposed to pressures from the social and humanitarian environment in the first place, followed by pressures from the scientific and research environment, then the organizational environment, and pressures from the administrative and financial environment, respectively, at varying levels. Which enabled us to conclude that there is ambiguity in tasks, roles, and overlapping work, in addition to the need to assign higher administrative levels and their moral and material support, and the college deanship can help in ensuring prevention and alleviating the severity of the pressures that teachers are exposed to in the dimensions and All functional environment. The most important recommendations that came out of the study emphasize giving priority and attention to teachers as a supreme value in the College of Physical Education and Sports Sciences, in addition to consolidating human relations and social connections and solving problems between colleagues in general, and teachers and students in particular, and ensuring the requirements for the success of quality Moral and material performance for teachers, in addition to all entitlements.